Radiotherapy for Low-Grade Astrocytomas - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The effect of radiotherapy on the survival of 143 children with low-grade (grade 1 or 2) astrocytomas was evaluated at the Royal Manchester Children's Hospital, and Christie Hospital and Holt Radium Institute, Manchester, UK.